(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s ((3Ydi Hf MSf s)
(3ChdgG (B:s
(3CNHGQ JCHW TQkG s
(3BNQgG (B:s
(3CNHGQ RgjQ GdcH s
(3GdfSNI GdJGSYI YTQs
(3gPG GdLRA ef fSNI OGQ GdcJH GdeUQjI Qbe(B579 (3GdecJhHI HNW eMeO Hf CHj WGdH GdHOQi SfI (B614 (3g`s
(3hQO CjVkG JMJ Qbe (B"2176"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B78s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B425 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B129s
Keywords: (3GdCOHs